16 Blood pressure reduction after catheter-based renal denervation in the absence of antihypertensive medications: spyral HTN-off med pivotal trial results. (30th September 2020) - Sharif, F; McGrath, B; O'Connor, T; Boehm, M; Fario, K; Kandzari, D; Mahfoud, F; Cusack, R
Abstract : Objective: The SPYRAL HTN-OFF MED Pivotal Trial was designed to assess the efficacy of renal denervation (RDN) to lower blood pressure (BP) in the absence of anti-hypertensive medications. Methods: In this international, randomized, sham-controlled trial, patients with hypertension and office systolic blood pressure (SBP) ≥150 mmHg and <180 mmHg were randomised 1:1 to RDN or sham control. Patients were required to abstain from anti-hypertensive medications prior to randomization. The primary efficacy endpoint was baseline-adjusted change in 24-hour SBP from baseline to 3 months. The secondary efficacy endpoint was baseline-adjusted change in office SBP from baseline to 3 months. Bayesian statistics were used to utilize evidence from the pilot and pivotal studies. Results: Patients were enrolled at 44 centres in 9 countries. A total of 331 patients were randomised to RDN (N=166) and sham control (N=165). The primary and secondary efficacy endpoints were met, with Bayesian posterior probability of superiority >0.999. The treatment differences were -3.9 mmHg for 24-hour SBP and -6·5 mmHg for office SBP between RDN and sham control groups. Treatment differences in 24-hour and office diastolic pressure at 3 months were -3.1 mmHg and -4.4 mmHg, respectively. Reductions in BP after RDN were consistent throughout 24 hours. There were no major procedural safety events to 3 months. Conclusions: Results from the SPYRAL HTN-OFF MED Pivotal trial, first reported at ACC2020, demonstrate the efficacy of catheter-based RDN compared to sham control to safely lower BP in the absence of anti-hypertensive medications.